2012
DOI: 10.1007/s10646-012-1021-1
|View full text |Cite
|
Sign up to set email alerts
|

Clone- and age-dependent toxicity of a glyphosate commercial formulation and its active ingredient in Daphnia magna

Abstract: Low levels of glyphosate based herbicide induced significant negative effects on the aquatic invertebrate Daphnia magna. Glyphosate herbicides such as brands of Roundup, are known to be toxic to daphnids. However, published findings on acute toxicity show significant discrepancies and variation across several orders of magnitude. To test the acute effects of both glyphosate and a commercial formulation of Roundup (hereafter Roundup), we conducted a series of exposure experiments with different clones and age-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
88
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 43 publications
(66 reference statements)
9
88
1
4
Order By: Relevance
“…As in the latter test Roundup systematically resulted in 25-100% higher effects than glyphosate at equivalent concentrations, the enhanced effect was attributed to POEA. Toxicity to the water flea (Daphnia magna) is of special importance, and not only formulated glyphosate-based herbicides (Cuhra et al, 2013;Ørsted and Roslev, 2015), but also glyphosate residues in GT soybean were shown to exert toxicity on this standard ecotoxicity indicator organism. Effects of glyphosate on somatic and ovarian growth, as well as of glyphosatebased formulations on ovarian growth and immune status of freshwater and estuarine crab species were reported (Hong et al, 2017;Avigliano et al, 2018;Canosa et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…As in the latter test Roundup systematically resulted in 25-100% higher effects than glyphosate at equivalent concentrations, the enhanced effect was attributed to POEA. Toxicity to the water flea (Daphnia magna) is of special importance, and not only formulated glyphosate-based herbicides (Cuhra et al, 2013;Ørsted and Roslev, 2015), but also glyphosate residues in GT soybean were shown to exert toxicity on this standard ecotoxicity indicator organism. Effects of glyphosate on somatic and ovarian growth, as well as of glyphosatebased formulations on ovarian growth and immune status of freshwater and estuarine crab species were reported (Hong et al, 2017;Avigliano et al, 2018;Canosa et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…Cuhra and co-workers tested chronic effects of glyphosate and Roundup and showed that environmental concentrations of 0.05-0.45 mg/l (active ingredient) cause negative effects on D. magna offspring size and reproduction (Cuhra et al 2013). Chemical residues of glyphosate and its primary metabolite, AMPA, are documented to be present in herbicide tolerant GM soy (Duke et al 2003;Bøhn et al 2014).…”
Section: The Daphnia Magna Modelmentioning
confidence: 99%
“…Effects of glyphosate are briefly summarized as the following: altered respiration in some eukaryotic organisms due to disruption of cytochrome function within the electron transport system; immobilization of nutrients essential for metabolic processes in microorganisms and plants; disruption of microbial diversity in plant rhizospheres; increase in potential root phytopathogens and suppression of beneficial antagonistic bacteria; inhibition of mycorrhizal spore germination leading to poor host plant infection and establishment of the symbiosis; reduced infection of legume roots by rhizobia leading to reduced nodulation required for symbiotic nitrogen fixation; disruption of earthworm activity; and reduction in growth and reproduction of numerous aquatic organisms including Daphnia spp. 10 as well as sediment-inhabiting organisms.…”
mentioning
confidence: 99%